Microsoft Excel functions and formulas - Held, Bernd; Moriarty, Brian; Richardson, Theodor (Mercury Learning and Information, 2018)
"In this completely updated edition covering Excel 2016 and previous versions, Microsoft Excel Functions & Formulas demonstrates the secrets of Excel through the use of practical and useful examples in a quick reference format. Easy to use and equipped with a variety of functions, Microsoft Excel is the tool of choice when it comes to crunching numbers, building charts, and analyzing tables. With over 250 Excel worksheet examples, files, and added video tutorials, the book is an excellent resource for all Excel users who want to understand, create, and apply formulas. Experienced users will also find Microsoft Excel Functions & Formulas an excellent reference for many of the program's advanced formulas and functions. The text is easy to understand with numerous step-by-step instructions and the actual, ready to use, Excel screenshots of the input and output from the formulas. A CD-ROM accompanies the book with video tutorials, worksheet files of examples for numerous functions, formulas, and all the figures from the text."-- Provided by publisher
Keywords: Microsoft Excel (Computer file); Electronic spreadsheets -- Computer programs.; Business -- Computer programs.; elektronické knihy; electronic books